Analysis of the Influence of Industrial Work Practice Experience (PRAKERIN) On the Entrepreneurial Interest of Vocational High School Students: Mediated by Self-Perception : Study on Vocational High School Students in Jombang District - Zahroh, Ainun; Ludi Wishnu Wardana; Nurika Restuningdiah (Social Science Studies, 2025)
Research Aims: This study aims to analyse how industrial work practice experience (PRAKERIN) influences vocational high school students' interest in entrepreneurship, particularly focusing on students in Jombang District. It also explores the role of self-perception as a mediating factor in this relationship. By examining students' experiences in real-world industrial settings, the study seeks to understand whether hands-on work exposure and self-assessment of skills and confidence gained from these experiences contribute to an increased desire to pursue entrepreneurship. This research can help educators and policymakers develop effective strategies to foster entrepreneurial interest among students in vocational education. Design/methodology/approach: This research uses a quantitative approach with Partial Least Squares structural equation modelling (PLS-SEM) to predict and confirm the given hypothesis. This research uses google form for data collection on students of the Digital Business Department of Public and Private Vocational Schools in Jombang Regency. Respondents in this study were 155 respondents from the three schools that were used as research objects. Research Findings: This study found that the experience of Industrial Work Practices (PRAKERIN) has a significant influence on the entrepreneurial interest of vocational students in the Digital Business expertise program in Jombang. PRAKERIN experience directly increases entrepreneurial interest and also strengthens students' self-perception. A stronger self-perception has a positive effect on students' entrepreneurial interest. In addition, self-perception acts as a significant mediator between PRAKERIN experience and entrepreneurial interest, indicating that PRAKERIN experience increases interest through improving students' self-perception. Theoretical Contribution/Originality: This study contributes to the understanding of how industrial work practice experience (PRAKERIN) affects vocational high school students' entrepreneurial interest, highlighting the role of self-perception as a mediator. By focusing on students in Jombang District, it offers original insights into how practical work exposure can shape students' career interests, specifically in entrepreneurship. This research adds to existing knowledge by showing that real-world experience, combined with students' self-assessment of skills, plays a significant role in motivating entrepreneurial pursuits, which can guide future educational and vocational training strategies.